THE MECHANISM OF THE PROCESS OF HYDROTUZATION OF DIESEL FUEL - Gʻulomov, Sh. T.; Yusupova, G. X.; Jumayev, M. Sh. (Молодёжный вестник Новороссийского филиала Белгородского государственного технологического университета им. В. Г. Шухова, 2024)
On an industrial scale, the quality of diesel fuel is improved in high-power hydrodesulfurization plant. The hydrodesulfurization process is carried out in solid catalysts of various compositions and properties. Aluminum-cobalt-molybdenum catalysts based on such metals are the most widely used in industry.In the hydrodesulfurization reactions of oil fractions for scientific and practical purposes, the chemical composition, structure, state and activity of such catalysts are widely studied, and the structural features of active centers are emphasized.